'Doctor, Doctor. . .' entrepreneurial diagnosis and market making. Issue 3 (13th May 2014) - GODLEY, ANDREW C.; CASSON, MARK C.
Abstract: Doctor-patient jokes are universally popular because of the information asymmetries within the diagnostic relationship. We contend that entrepreneurial diagnosis is present in markets where consumers are unable to diagnose their own problems and, instead, rely on the entrepreneur to diagnose them. Although it is widely recognized that consumers face information asymmetries over price comparison and quality assessment, little attention has been given to information asymmetries regarding individual customers' needs. This has led to the economic contribution of the diagnostic entrepreneur being overlooked. Entrepreneurial diagnosis is a cognitive skill possessed by the entrepreneur. It is a subset of entrepreneurial judgment and can be modeled. The model shows that in order to exploit opportunities it is often necessary for entrepreneurs to invest in market-making activities, such as customer-focused diagnostic services, backed up by credible reputations for competence and integrity. While diagnostic entrepreneurship is particularly important in knowledge-intensive service industries (such as medicine) it is important in all industries whenever radical product innovation occurs (e.g. modern computers and phones). Successful commercialization of innovation often requires, not only new technology, but diagnostic entrepreneurship too.